Challenges and possibilities in offering support to family caregivers to persons with dementia of non-European background: A qualitative study - Aber Sharon Kagwa; Kirsi Tiitinen Mekhail; Åsa Gransjön Craftman; Hanne Konradsen; Zarina Nahar Kabir; Marie Tyrrell (PLoS ONE, 2026)
Background With population ageing and increasing ethnic diversity in Europe, it is essential to support the growing number of family caregivers (FCs) who provide daily care for persons living with dementia. In Sweden, social care professionals have a vital role in providing formal support to family caregivers within municipalities. Previous research indicates challenges for social care professionals in reaching family caregivers to persons with dementia with immigrant backgrounds. However, there is still a lack of evidence explaining why these FCs do not use available support services to the same extent as their ethnic Swedish peers. This study aimed to explore social care professionals’ perspectives on challenges and possibilities in offering support to family caregivers to community-dwelling persons with dementia of non-European background. Methods An explorative qualitative design was used. The data were collected through semi-structured interviews with thirteen community-based social care professionals in Sweden. The data were analysed using Systematic Text Condensation. Findings Eight themes emerged from the analysis: (i) Mistrust in the system, (ii) Hard-to-Reach group, (iii) Misalignment of expectations and reality, (iv) Stigmatised situations, (v) Timely contact, (vi) Communicating with the younger generation, (vii) Promoting and adapting support, and (viii) Coordination of services. Conclusions The results indicate that culturally sensitive and tailor-made support can help build and maintain trust among family caregivers of non-European backgrounds and increase the uptake of offered support. Collaboration between formal and informal societal actors and community outreach through various channels, in multiple languages, can raise awareness of available support to family caregivers and increase accessibility to groups with diverse immigrant backgrounds.